ANALISIS POTENSI USAHA TERNAK DOMBA UNTUK MENINGKATKAN KETAHANAN PANGAN MASA PANDEMI COVID-19 DI KECAMATAN PADANG BOLAK - Ricca Sari; Resti Rianita; Aulia Arum Chandra Kartika (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to identify and analyze the potential for developing sheep in Padang Bolak District. The results showed that Padang Bolak District is an area that can be used as a center for sheep development, where the LQ value is 1.95942 with the economic density of sheep included in the rare category, namely 49.87 (< 50). The density of sheep farming in Padang Bolak District is still in the medium category, namely 0.74 (0.25-1). The density of sheep area is also included in the rare category of 4.72 while the availability of forage that can be produced by Padang Bolak District is 360,175 tons of dry matter per year. The sheep that can be produced based on the capacity of the Padang Bolak District are 2,466,777 ST. The results of the Carrying Capacity Index (IDD) assessment of Padang Bolak District are 1.00007, which means that this value is included in the critical area category so that the development of sheep with the LEISA concept cannot be developed in this sub-district.